Cyberbullying issues on a transgender Instagram account - Suwastini, Ni Komang Arie; Widiastuti, Ni Putu Santhi; Adnyani, Ni Luh Putu Sri; Mahayanti, Ni Wayan Surya; Asril, Nice Maylani (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2024)
Critical Discourse Analysis (CDA) of Fairclough was employed to analyze discourse regarding cyberbullying on Millen Cyrus's Instagram account, which has claimed herself as transgender. Most of the comments show negative responses. Some linguistic features are analyzed, such as 'bro,' 'laki,' 'tulen,' 'banci,' and many more, which refer to cyberbullying. With the sophisticated features of Instagram, it is no wonder that news could get about quickly. In the context of the situation, Millen could not avoid any attention from the media and the public as she is a part of Ashanty's family, an Indonesian singer and socialite. At the instructional level, it is easy to get more exposure from others since her account has been verified by Instagram, including Millen's followers and non-followers, as people quickly found her posts on the explore feature. The act of some people who put comments on a transgender account, like what they have done to Millen Cyrus, has also evidenced that their discourse is influenced by the existence of their culture, religion, family background, and so on.